2015
DOI: 10.9738/intsurg-d-13-00211.1
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Levels in Bowel Strangulation With Experimental Animal Model

Abstract: Bowel strangulation is a common disease and often requires an urgent operation. Our previous report showed that lactate concentration in the blood is a good predictive marker for emergency. However, the alteration in lactate levels during the course of bowel strangulation remains unclear. We have investigated the progressive increase of lactate after induction of bowel strangulation with animal experiments. Thirty-six mice were randomly divided into 6 groups: 0, 8, 16, 24, 48, and 72 hours after operation. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Lactate is a product of the anaerobic metabolism of glucose ( Tanaka et al, 2015 ). Lactase from ingested lactic acid bacteria may enhance the hydrolysis of lactose to glucose and galactose in the small intestine, which is rapidly absorbed or fermented ( Hove et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lactate is a product of the anaerobic metabolism of glucose ( Tanaka et al, 2015 ). Lactase from ingested lactic acid bacteria may enhance the hydrolysis of lactose to glucose and galactose in the small intestine, which is rapidly absorbed or fermented ( Hove et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…On admission, the patient’s lactate level (2.9 mmol/L) did not really correlate with his clinical status nor intraoperative findings. Although increased lactate is associated with strangulated bowel, the level can lag by 8 h [ 5 ]. In terms of imaging modality, CT is the most reliable with the classical whirlpool sign.…”
Section: Discussionmentioning
confidence: 99%
“…During conditions of ischemic hypoxia, such as bowel ischemia, oxygen-deprived cells will adopt anaerobic glycolysis, and the level of serum lactate will rise [ 8 , 11 ]. Studies have suggested its potential as a biomarker of intestinal ischemia [ 12 , 13 ], and the World Society of Emergency Surgery (WSES) guidelines for the management of acute mesenteric ischemia state that while no laboratory parameters are sufficiently accurate to conclusively identify ischemic bowel, elevated L-lactate may assist [ 14 ]. This study aimed to evaluate the utility of serum L-lactate as a predictor of bowel ischemia in patients with intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%